Characterization of Calcinated Ni–Cu Ferrite Nanoparticles Synthesized by Citrate-gel Auto combustion Technique - Ibrahim F. Waheed; Thuraya Yarb Sabri; Najat A. Dahham; Faten Haithum Mulud (Iraqi Journal of Science, 2021)
Citrate-gel auto combustion technique was used to synthesize nickel-copper mixed ferrite nanoparticles NixCu1-xFe2O4 (x= 0.0, 0.4, 1.0) with different calcinating temperatures (200, 450, 650 and 850 °C). Structural, morphological, magnetic, and electrical properties were studied using X-ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), vibrating sample magnetometer (VSM), and LCR meter in order to determine significant influences of Cu2+ cations content in nickel ferrite. The XRD patterns showed that all compositions had cubic spinels, except CuFe2O4 samples. The system structure in Cu-ferrite was deformed at 650 °C from a cubic to a tetragonal system with a secondary phase CuO. Lattice constant was decreased with increasing Cu2+ cations substitution in Ni-ferrites, while crystalline volume was increased. With the help of Debye-Scherrer`s equation using XRD data, we found that the crystallite size at 850 °C is lying in the range from 38.70 to 48.00 nm. The FTIR spectrum of samples under investigation showed two significant absorption bands, which refer to the formation of a single-phase cubic spinel. The magnetization test revealed a soft ferromagnetic behavior for all the compositions sintered at 850 °C. The saturation magnetization (Ms) was decreased with the substitution by Cu2+ cations, while remnant magnetization (Mr) and coercivity (Hc) were increased in Cu-ferrite. The highest Ms value was 42.25 emu.g-1 for Ni-ferrite, while the highest Hc value was 517.16 Oe for Cu-ferrite. The electrical measurement of samples showed an increase in the real dielectric constant and AC conductivity at a frequency range of 20Hz-3MHz with the addition of copper cations.